Food restriction promotes downregulation of myocardial L-type Ca2+ channels - De Tomasi, Loreta Casquel [UNESP]; Bruno, Alessandro [UNESP]; Sugizaki, Mario Mateus [UNESP]; Lima-Leopoldo, Ana Paula [UNESP]; Nascimento, Andre Ferreira [UNESP]; de Oliveira Junior, Silvio Assis [UNESP]; Pinotti, Matheus Fecchio [UNESP]; Padovani, Carlos Roberto [UNESP]; Leopoldo, Andre Soares [UNESP]; Cicogna, Antonio Carlos [UNESP] (Canadian Science Publishing, Nrc Research Press, 2009)
Food restriction (FR) has been shown to impair myocardial performance. However, the mechanisms behind these changes in myocardial function due to FR remain unknown. Since myocardial L-type Ca2+ channels may contribute to the cardiac dysfunction, we examined the influence of FR on L-type Ca2+ channels. Male 60-day-old Wistar rats were fed a control or a restricted diet (daily intake reduced to 50% of the amount of food consumed by the control group) for 90 days. Myocardial performance was evaluated in isolated left ventricular papillary muscles. The function of myocardial L-type Ca2+ channels was determined by using a pharmacological Ca2+ channel blocker, and changes in the number of channels were evaluated by mRNA and protein expression. FR decreased final body weights, as well as weights of the left and right ventricles. The Ca2+ channel blocker diltiazem promoted a higher blockade on developed tension in FR groups than in controls. The protein content of L-type Ca2+ channels was significantly diminished in FR rats, whereas the mRNA expression was similar between groups. These results suggest that the myocardial dysfunction observed in previous studies with FR animals could be caused by downregulation of L-type Ca2+ channels.
Keywords: food restriction; papillary muscle; L-type calcium channels function; L-type calcium mRNA; L-type calcium protein; diltiazem; rate